Food security and women’s well-being: Insights from rural Nepal - Alvi, Muzna; Barooah, Prapti (All India Disaster Mitigation Institute (AIDMI), 2021)
As the impacts of the COVID-19 continue to be felt across the world, the need to address the vulnerabilities of the poor and marginalized is heightened. In rural and agriculture dependent economies, it is often the farm sector that is most severely impacted in times of crisis, in large part due to the lack of access to risk and loss mitigation measures, and limited access to government assistance. Among those who are affected, periods of crisis are often worse for vulnerable groups such as children, women and those belonging to historically disadvantaged groups and communities. We use four rounds of phone survey data from farmers in Nepal conducted between June 2020 to January 2021, to study the impacts of the pandemic and associated lockdowns on maize farmers in Dang district of Nepal, with a focus on food security and dietary diversity. Our sample comprises of nearly 690 respondents, of which 70% are women. The area where our survey is conducted, borders India and thus sees large out-migration of men, leaving women as de-facto heads of households.